Pembinaan Profesi Guru Pendidikan Agama Islam dalam Mengadaptasi Siswa Generasi Abad 21 - Ishak Syairozi (Universitas Indraprasta PGRI Jakarta, 2022)
The purpose of this study was to discover the patterns of teacher development in Islamic religious education through the organization of the MGMP teacher Training and Education organized by the Directorate of Islamic Religious Education at the Ministry of Religion in improving teacher professionalism so that they could adapt the teaching of 21st century students as well as find a training theory that can be implemented in an effort to increase the professionalism of Islamic religious education teachers. This study uses a phenomenological qualitative research approach. The data collected is based on the phenomena that occur in the process of training Islamic religious education teachers, including PAI teachers, organizations and related educational and training institutions and informants. The data collection techniques used are; observation, interviews, documentation, and data validation. Furthermore, it is processed and analyzed using the Miles and Huberman analytical framework which uses the terms data collection, data reduction and data display. This research resulted in a Konstis coaching theory, which reads: